Efficacy of liquid nitrogen cryotherapy for Barrett's esophagus after endoscopic resection of intramucosal cancer: A multicenter study. Issue 2 (26th January 2018) - Trindade, Arvind J; Pleskow, Douglas K; Sengupta, Neil; Kothari, Shivangi; Inamdar, Sumant; Berkowitz, Joshua; Kaul, Vivek
Abstract: Background and Aim: Liquid nitrogen cryotherapy (LNC) allows increased depth of ablation compared with radiofrequency ablation in Barrett's esophagus (BE). Expert centers may use LNC over radiofrequency ablation to ablate Barrett's esophagus after endoscopic resection of intramucosal cancer (IMCA). The aim of our study was to (1) evaluate the safety and efficacy of LNC ablation in patients with BE and IMCA and (2) to evaluate the progression to invasive disease despite therapy. Methods: This was a multicenter, retrospective study of consecutive patients with BE who received LNC following endoscopic mucosal resection (EMR) of IMCA. The outcomes evaluated were complete eradication of dysplasia and intestinal metaplasia and development of invasive cancer during follow up. The follow‐up period was at least 1 year from initial LNC. Results: Twenty‐seven patients were identified. The median Prague score was C3M5 (range C0M1–C14M14). After EMR+LNC, the median Prague score was C0M1 (range C0M0–C9M10); 22/27 patients (82%) achieved complete eradication of dysplasia after cryotherapy, and 19/27 patients (70%) achieved complete eradication of intestinal metaplasia. One out of 27 patients (4%) developed invasive cancer (disease beyond IMCA) over the study period. Conclusion: Cryotherapy is an effective endoscopic tool for eradication of BE dysplasia after EMR for IMCA. Development of invasive cancer is low for this high‐risk group.